Photovoltaic enhancement by Au surface-plasmon effect for La doped BiFeO3 films. Issue 40 (9th October 2017) - Li, F. Z.; Zheng, H. W.; Zhu, M. S.; Zhang, X. A.; Yuan, G. L.; Xie, Z. S.; Li, X. H.; Yue, G. T.; Zhang, W. F.
Abstract : Herein, the photovoltaic (PV) effect of ferroelectric Bi0.85 La0.15 FeO3 (BLFO) films fabricated through a sol–gel method is investigated. Abstract : Herein, the photovoltaic (PV) effect of ferroelectric Bi0.85 La0.15 FeO3 (BLFO) films fabricated through a sol–gel method is investigated. The ferroelectric properties of the BLFO films improve compared to the undoped BiFeO3 films. The application of Au nanoparticles (AuNPs) increases the open circuit voltage ( V OC ) and short circuit current density ( J SC ) from 0.2 V to 0.3 V and 5.3 μA cm −2 to 18.5 μA cm −2, respectively, which could be attributed to Au surface-plasmon effects. The PV output for the BLFO film can be modulated after applying external poling voltages. Considering the ferroelectric polarization and plasmonic effects, a plausible theoretical model is constructed to depict the physical mechanism of PV enhancement for the BLFO film in detail. This work not only presents a new approach to improve the PV effect of ferroelectric films but also provides important insights into the PV mechanism of ferroelectric films.